Enhancing Home Security with IoT Devices: A Vulnerability Analysis Using the IoT Security Test - Misailov Andrey Yu.; Mishra Neeti; Lakhanpal Sorabh; Prakash Anshika; Sharma Naresh (BIO Web of Conferences, 2024)
In order to carefully evaluate the susceptibility of common IoT devices found in smart homes, this research made use of the IoT Security Test framework. The findings showed a significant average drop in vulnerability ratings of 45% after evaluation, clearly indicating that improving IoT device security is feasible. The research classifies vulnerabilities found, highlighting the prevalence of Firmware Problems, Weak Passwords, and Network Vulnerabilities. Moreover, it examines the efficacy of remedial initiatives. These discoveries play a crucial role in enhancing the security of Internet of Things devices, providing a strong barrier for the protection of homeowners and the privacy of their data, especially in the constantly linked world of smart homes.